The kinetics of ferrous iron oxidation by Leptospirillum-like bacteria in absence and in presence of pyrite and pyrite/arsenopyrite mixtures in continous and batch cultures - Van Scherpenzeel, Dorothee Agnes (Department of Chemical Engineering, 2026)
The leaching process of pyrite and pyrite/arsenopyrite in presence of bacteria is considered a 2-step mechanism, in which i) the mineral sulphide is chemically leached by ferric iron into the metal ion and sulphate and ii) the bacteria regenerate ferric iron. The kinetic parameters of these subprocesses are determined in presence of Leptospirillum-like bacteria as the main ferrous iron oxidizing bacterium. The bacterial regeneration of ferric iron was determined in a continuous culture with a feed solution of 12 gÂ· l-1 ferrous iron. The pyrite and pyrite/arsenopyrite leaching in presence of bacteria was followed in a batch culture whereby in the exponential growth phase pyrite, resp. pyrite/arsenopyrite was added in stages. Unique of this method is that the process is followed by the off-gas analysis and redox potential of the solution. With the off-gas analysis the oxygen and carbon dioxide concentration in the incoming air and outcoming gas was measured and the ferrous iron concentration in the solution was derived with the redox potential. The bacterial ferrous iron oxidation followed modified Monod kinetics with the redox potential as driving force.